Structural Alterations of Segmented Macular Inner Layers in Aquaporin4-Antibody-Positive Optic Neuritis Patients in a Chinese Population - Peng, Chunxia; Wang, Wei; Xu, Quangang; Zhao, Shuo; Li, Hongyang; Yang, Mo; Cao, Shanshan; Zhou, Huanfen; Wei, Shihui (PloS one, 2016)
This study aimed to analyse the structural injury of the peripapillary retinal nerve fibre layer (pRNFL) and segmented macular layers in optic neuritis (ON) in aquaporin4-antibody (AQP4-Ab) seropositivity(AQP4-Ab-positiveON) patients and in AQP4-Ab seronegativity (AQP4-Ab-negative ON) patients in order to evaluate their correlations with the best-corrected visual acuity (BCVA) and the value of the early diagnosis of neuromyelitis optica (NMO). This is a retrospective, cross-sectional and control observational study. In total, 213 ON patients (291 eyes) and 50 healthy controls (HC) (100 eyes) were recruited in this study. According to a serum AQP4-Ab assay, 98 ON patients (132 eyes) were grouped as AQP4-Ab-positive ON and 115 ON patients (159 eyes) were grouped as AQP4-Ab-negative ON cohorts. All subjects underwent scanning with spectralis optical coherence tomography (OCT) and BCVA tests. pRNFL and segmented macular layer measurements were analysed. The pRNFL thickness in AQP4-Ab-positive ON eyes showed a more serious loss during 0-2 months (-27.61μm versus -14.47 μm) and ≥6 months (-57.91μm versus -47.19μm) when compared with AQP4-Ab-negative ON eyes. AQP4-Ab-positive ON preferentially damaged the nasal lateral pRNFL. The alterations in the macular ganglion cell layer plus the inner plexiform layer (GCIP) in AQP4-Ab-positive ON eyes were similar to those in AQP4-Ab-negative ON eyes. AQP4-Ab-positive ON eyes had entirely different injury patterns in the inner nuclear layer (INL) compared with AQP4-Ab-negative ON eyes during the first 6 months after the initial ON attack. These differences were as follows: the INL volume of AQP4-Ab-positive ON eyes had a gradual growing trend compared with AQP4-Ab-negative ON eyes, and it increased rapidly during 0-2 months, reached its peak during 2-4 months, and then decreased gradually. The pRNFL and GCIP in AQP4-Ab-positive ON eyes had positive correlations with BCVA. When the pRNFL thickness decreased to 95%CI (50.77μmto 60.85μm) or when the GCIP volume decreased to 95%CI (1.288 mm3to 1.399 mm3), BCVA began to be irreversibly damaged. The structural alterations of pRNFL and GCIP could indicate the resulting visual damage. In addition, the injury pattern of INL could be a potential structural marker to predict the conversion of ON to NMO.